Techno-economic analysis of clean cooking technologies and fuels in Uganda (Archives of Agriculture and Environmental Science, 2025)
Access to clean, affordable, and efficient cooking energy is a key development challenge in Uganda, with over 90% of households and institutions relying on traditional biomass fuels. This study was focused on techno-economic assessment of cooking technologies and fuels through Controlled Cooking Tests (CCTs), surveys, and interviews across household and institutional settings to evaluate fuel consumption, cooking time, cost, and user preferences across wood, charcoal, briquettes, LPG, and electric stoves. The results showed that electric hot plates and LPG stoves were the most energy-efficient, consuming 10.42 MJ and 13.28 MJ, respectively, cooking of 1 kg of beans compared to 38.81 MJ for improved wood stoves and 102.44 MJ for traditional three-stone fires. Cooking time, the improved institutional wood stove was the fastest (129 min), followed by LPG (151 min), traditional stoves (153 min), and electric hot plates (174 min). Fuel cost per kg of beans cooked was highest for LPG (Ugx 5,506) and electricity (Ugx 4,393), while improved briquette stoves were the cheapest (Ugx 302), though their adoption remains limited due to availability issues. Improved biomass stoves demonstrated up to 62% energy savings compared to traditional devices, offering a cost-effective and scalable transition option. This study provides the first comprehensive performance comparison across multiple fuel-stove combinations in Uganda and highlights critical trade-offs between energy efficiency, cost, and accessibility. Strategic policy actions including targeted subsidies, investment in clean fuel supply chains, and behaviour change campaigns are recommended to accelerate adoption and support Uganda’s energy, climate, and development goals.